Case management of young patients with temporomandibular Osteoarthritis joint disorders using stabilization splint,self-therapy, and chondroitin sulfate-glucosamine supplements - Uliani, Hanna Mentari; Ricca Chairunnisa; Syafrinani (Indonesia Prosthodontic Association, 2024)
Introduction: Osteoarthritis (OA) is a disorder of the temporomandibular joint which results in permanent changes to TMJ. Scissors bite and bad habits are one of the etiological factors of OA. OA causes deviation when opening the mouth, limitations of mouth opening, and joint crepitus sounds. Use of stabilization splints (SS), physical therapy, and consumption of chondroitin sulfate-glucosamine supplements aimed at reducing joint pain, relaxing TMJ muscle, and preventing joint damage. Case report: A 22-year-old female patient came to North Sumatera of Dental Hospital with complaints stiff jaw when opening her mouth, especially in the morning. Complaints of pain occurred since skelling treatment 3 years ago. Clinical examination showed scissors bite and a habit of chewing on the right side. Palpation of the right anterior temporalis muscle revealed familiar pain and joint crepitus sound. Based on DC/TMD assessment, the patient had OA where the mouth opening is 35 mm without pain and 38 mm with pain accompanied by a left deviation of 1.5 mm. On CBCT examination there was flattening on the TMJ surface. Treatment is carried out by using SS every day and consuming chondroitin sulfate-glucosamine supplements once a day accompanied by self-therapy. Self-therapy is carried out alone by practicing opening and closing the jaw for 15 minutes every day. After 6 months is obtained without assisted mouth opening of 36 mm to 41 mm. There is no pain on palpating muscles but there is still a crepitus sound when opening and closing the mouth. Conclusion: Treatment of OA with SS, self-therapy, and consumption of Chondroitin Sulfate-Glucosamine supplements is effective in reducing TMJ joint pain and muscle stiffness through chondroitin stimulation mechanism so that prevents further degenerative processes. Keywords: Temporomandibular joint disorder, Osteoarthritis, Stabilization splints, Cone beam computed tomography, Chondroitin sulfate-glucosamine.